2019
DOI: 10.1521/pedi_2018_32_347
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy and Internalizing Psychopathology: A Triarchic Model Perspective

Abstract: Methodological and conceptual differences across studies have impeded our understanding of the relationship between psychopathy and internalizing psychopathology. To shed further light on this question, we undertook correlational and structural-modeling analyses of data from two samples to characterize how facets of psychopathy relate to internalizing psychopathology when assessed using multidimensional measures of each construct (i.e., Triarchic Psychopathy Measure, Inventory of Depression and Anxiety Symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 74 publications
(95 reference statements)
12
45
0
Order By: Relevance
“…Furthermore, within a male offender substance treatment sample, these authors found that boldness was associated to a strong negative degree with social anxiety, and to a more moderate negative degree with reported depressivity/dysphoria. More recently, in two separate samples, one utilizing self-report and the other informant-report assessments, Latzman et al (2019) found a similar pattern of associations across samples. That is, boldness evidenced clear negative associations with general depression, dysphoria, and social anxiety, to a similar degree in the self-report sample, and to an even stronger degree in the informant-report sample.…”
Section: Triarchic Trait Dimensionsmentioning
confidence: 73%
See 2 more Smart Citations
“…Furthermore, within a male offender substance treatment sample, these authors found that boldness was associated to a strong negative degree with social anxiety, and to a more moderate negative degree with reported depressivity/dysphoria. More recently, in two separate samples, one utilizing self-report and the other informant-report assessments, Latzman et al (2019) found a similar pattern of associations across samples. That is, boldness evidenced clear negative associations with general depression, dysphoria, and social anxiety, to a similar degree in the self-report sample, and to an even stronger degree in the informant-report sample.…”
Section: Triarchic Trait Dimensionsmentioning
confidence: 73%
“…Disinhibition relates robustly and positively to anxiousness/distress and more modestly with fear symptomatology. Finally, although meanness exhibits modest positive associations with some fear-disorder symptoms such as social phobia and some distress-disorder symptoms such as general depression, this appears to be largely attributable to its overlap with disinhibition (Latzman et al, 2019; Patrick & Drislane, 2015). This pattern of results is interesting to consider from the standpoint of the triarchic constructs as core biobehavioral traits.…”
Section: Triarchic Trait Dimensionsmentioning
confidence: 94%
See 1 more Smart Citation
“…These authors also tested single scale bifactor models but did not examine a bifactor model across the entire TriPM item set. Like Latzman et al (2019), Somma et al also employed correlated residual errors within a correlated three-factor model to achieve adequate fit. If, as reported, they allowed error correlations between items loading .20 or greater on the same factor, to account for distinct subfactor loadings, then the final model included 121 such error correlations; if the decision was based on loadings of |.20| or greater then 174 such error correlations were estimated.…”
Section: Tripm Item-level Latent Structurementioning
confidence: 99%
“…The current study tested the structure of the TriPM via itemlevel exploratory and confirmatory factor analyses (EFA, CFA) in multiple, large, online, community and offender samples from North America and Europe. We expected the item-level threefactor model would evidence poor fit based on previous research (Latzman et al, 2019;Shou et al, 2018;Somma et al, 2018). Following the methodology of Somma et al (2018), we initially examined the items within each TriPM scale separately and expected multiple dimensions (factors) would emerge from each of the three TriPM domains.…”
Section: Tripm Item-level Latent Structurementioning
confidence: 99%